Anti-transcription intermediary factor 1-gamma IgG2 isotype is associated with cancer in adult dermatomyositis: an ENMC multinational study. (17th October 2022) - Cordel, Nadège; Dechelotte, Benoît; Jouen, Fabienne; Lamb, Janine A; Chinoy, Hector; New, Paul; Vencovsky, Jiri; Mann, Herman; Galindo-Feria, Angeles S; Dani, Lara; Selva-O'Callaghan, Albert; Werth, Victoria P; et al.
Abstract: Objective: To assess the role of the anti-TIF1γ auto-antibody (aAb) IgG2 isotype as a biomarker of cancer in anti-TIF1γ aAb-positive adult DM. Methods: International multicentre retrospective study with the following inclusion criteria: (i) diagnosis of DM according to ENMC criteria; (ii) presence of anti-TIF1γ IgG aAb determined using an in-house addressable laser bead immunoassay (ALBIA) from cryopreserved serums sampled at time of DM diagnosis and (iii) available baseline characteristics and follow-up data until the occurrence of cancer and/or a minimum follow-up of 1 year for patients without known cancer at diagnosis. Detection and quantification of anti-TIF1γ IgG2 aAb was done using the in-house ALBIA. In addition, a recent ELISA commercial kit was used for anti-TIF1γ IgG aAb quantification. Results: A total of 132 patients (mean age 55±15 years) of whom 72 (54.5%) had an associated cancer were analysed. The association between the presence of cancer and the presence of anti-TIF1γ IgG2 aAb was statistically significant ( P  = 0.026), with an OR of 2.26 (95% CI: 1.10, 4.76). Patients with cancer displayed significantly higher anti-TIF1γ IgG2 aAb ALBIA values with a median value of 1.15 AU/ml (IQR: 0.14–9.76) compared with 0.50 AU/ml (IQR: 0.14–1.46) for patients without cancer ( P  = 0.042). In addition, patients with cancer displayed significantly higher anti-TIF1γ IgG aAb ELISA values with a median value of 127.5 AU/ml (IQR: 81.5–139.6) compared with 93.0 AU/ml (IQR: 54.0–132.9) for patients without cancer ( P  = 0.004). Conclusion: These results suggest considering anti-TIF1γ IgG2 ALBIA and IgG ELISA values as biomarkers of cancer in anti-TIF1 γ aAb-positive adult DM.